Utilização da farinha de linhaça (Linum usitatissimum L.) no processamento de biscoito tipo "cracker": características físico-químicas, nutricionais e sensoriais. - Maciel, Leda Maria Braga (2006)
In the last decade the consumption of flaxseed (Linum usitatissimum L.) is increasing and awaking the interest of many searchers because it contains functional compounds as alphalinolenic acid, lignans and fibers related to its beneficial potential for health. Several studies confirmed the benefits of food enriched with flaxseed in prevention and treatment of several diseases as vascular disease, cancer, diabetes, arthritis, lupus, symptoms of menopause and post menopause, constipation, etc. The purpose of this work was to develop biscuits like cracker, added 10%, 15% and 20% of flaxseed flour (CL10, CL15 and CL20) from the formulation without addition of flaxseed flour (CSL) and evaluate its physical, chemical, instrumental, rheological and sensory characteristics. The flaxseed flour provoked significant changes in rheology of dough, improving the thickness, length and width parameters of crackers. The Tuckey test showed that the humidity of sample CL10 didn’t differ to the level (p<0,5) of crackers CSL, CL15 and CL20, however the CSL cracker differed of CL15 and CL20 crackers. The most meaningful changes in the composition of crackers were verified in lipids and protein content. All crackers with addition of flaxseed flour showed darker than CSL cracker. 96 panelists as for appearance, color, flavor, texture, global acceptance, purchase intent and ideal scale for texture assessed the acceptability of crackers. There was a meaningful difference among the formulations (p<0,5) in all attributes, excepting CSL and CL20 crackers. The results of purchase intent suggested that the consumers had a major interest on acquisition of CL15 crackers. The addition of flaxseed flour provoked significant increases on protein, mineral salts and fibers contents of crackers, transforming them in a product with high content of alimentary fibers.